Special immune-related adverse events and subsequent photodynamic therapy in tislelizumab treatment for esophageal cancer: a case report - Li, Longzhao; Bian, Lingjie; Kou, Na; Yuan, Yue; Zou, Heng (Frontiers in Immunology, 2024)
This case report highlights the immune-related adverse events (irAEs) that occurred during the treatment of esophageal cancer with Tislelizumab and discusses management strategies, indicating that photodynamic therapy (PDT) may be an optimal adjunctive treatment option. Following Tislelizumab therapy, the patient demonstrated significant tumor reduction; however, subsequent irAEs related to immunotherapy emerged, including eyelid muscle weakness and myocardial and skeletal muscle injury. Methylprednisolone successfully alleviated these symptoms, with early intervention being crucial for controlling irAEs. The patient then underwent PDT, which not only further helped manage irAEs but also inhibited tumor progression. This case underscores the specific adverse reactions, such as eyelid ptosis, skeletal muscle, and myocardial damage associated with Tislelizumab, and the importance of early corticosteroid intervention. It also emphasizes the significance of PDT as an adjunctive treatment for controlling tumors and alleviating immune-related adverse reactions.